2005
DOI: 10.1007/11527886_43
|View full text |Cite
|
Sign up to set email alerts
|

User- and Community-Adaptive Rewards Mechanism for Sustainable Online Community

Abstract: Abstract. Abundance of user contributions does not necessarily indicate sustainability of an online community. On the contrary, excessive contributions in the systems may result in "information overload" and user withdrawal. We propose an adaptive rewards mechanism aiming to restrict the quantity of the contributions, elicit contributions with higher quality and simultaneously inhibit inferior ones. The mechanism adapts to the users preferences with respect to types of contributions and to the current needs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 6 publications
0
62
0
7
Order By: Relevance
“…The first incentive mechanism applied in Comtella (Bretzke and Vassileva 2003;Cheng and Vassileva 2005a) rewarded users with points for actions that were beneficial for the community (contributing new papers, downloading papers from others and making them available for sharing with others). These were actions that the user had full control of and did not reflect the opinion of other users of the user's actions.…”
Section: Challenge In Selecting What User Actions To Reward With Repumentioning
confidence: 99%
See 1 more Smart Citation
“…The first incentive mechanism applied in Comtella (Bretzke and Vassileva 2003;Cheng and Vassileva 2005a) rewarded users with points for actions that were beneficial for the community (contributing new papers, downloading papers from others and making them available for sharing with others). These were actions that the user had full control of and did not reflect the opinion of other users of the user's actions.…”
Section: Challenge In Selecting What User Actions To Reward With Repumentioning
confidence: 99%
“…The results of the evaluation of this mechanism showed a significant but short-term increase of participation. There were attempts by some users to game the system, by performing unreasonably high numbers of the rewarded actions (Cheng and Vassileva 2005a). Since the quality of the contributions was not evaluated, the users' participation in the system deteriorated due to the overwhelming amount of low-quality contributions and the resulting cognitive overload (Jones and Rafaeli 1999).…”
Section: Challenge In Selecting What User Actions To Reward With Repumentioning
confidence: 99%
“…While collaborative filtering mechanisms are mostly used in collaborative Web recommender systems reviewed in Chapter 9 of this book [71], a few of systems used it for providing social navigation support. A straightforward example of navigation support based on community ratings is provided by collaborative resource gathering systems such as CoFIND [39] or COMTELLA [26], which were reviewed in section 8.3.2 above. A more elaborate example is shown by the CourseAgent system [42].…”
Section: Social Mechanismsmentioning
confidence: 99%
“…In this situation the "conceptually stable" ordering offered by link sorting can become an attractive solution. Good examples of this may be found among adaptive news systems reviewed in Chapter 18 of this book [3] and collaborative resource gathering systems such as CoFIND [39] or COMTELLA [26]. Adaptive news systems typically present links to recommended news articles in a single list or on several pages by category.…”
mentioning
confidence: 99%
“…Recent experimentation in learning networks have shown that incentive mechanisms like the adaptive introduction of extra (bonus) material based on contributions can increase both active and passive participation in learning networks [10]. Beside the individual activity adaptive rewarding mechanisms [3] could also take into account the current needs of the community and the style and quality of individual contributions in the past.…”
Section: Social Exchange Theory Reinforcement Mechanisms and Learninmentioning
confidence: 99%